Relationship of Teacher Performance to Student Satisfaction in Islamic Education Learning Process at SMAN 1 Canduang - Yusra, Yusra; Sesmiarni, Zulfani (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
The purpose of this study was to identify and analyse the relationship between teacher performance and student satisfaction in PAI learning at SMAN 1 Canduang. This study used a quantitative approach with a correlational method to identify the relationship between teacher performance and student satisfaction in PAI learning at SMAN 1 Canduang. The results of this study indicate that there is a highly correlated relationship although at a very low level. Teacher performance does play a role in providing satisfaction to students in PAI learning. The product moment correlation calculation of 0.147 indicates that teacher performance, although with a low influence, still has a positive impact on student satisfaction. This indicates that improving teacher performance through more effective teaching methods, better interaction, and delivery of interesting material can increase student satisfaction. In addition, other factors such as learning environment, school facilities, and support from parents also need to be considered to improve overall student satisfaction. Further research is needed to explore other factors that influence student satisfaction and develop more effective strategies in improving teacher performance and creating a more satisfying learning environment for students.